(untitled) (Canadian Hematology Today, 2024)
Multiple myeloma is characterized by clonal proliferation of biologically heterogeneous plasma cells, leading to diverse clinical presentations and outcomes. Although outcomes have improved dramatically over the past decade with the rapid change in the treatment paradigm in standard-risk myeloma, a subset of patients remains who respond poorly to treatment and experience early relapses. These patients are considered high-risk and can be identified at the time of diagnosis based on several factors and their response to treatment (Table 1). Therefore, it is important to consider high-risk status as a dynamic assessment.